C-Reactive Protein-to-Lymphocyte Ratio as a Prognostic Biomarker in Acute Ischemic Stroke Patients Undergoing Mechanical Thrombectomy: A Multicenter Study - Dogan, Hasan; Ozmuk, Ozkan; Memis, Zulfikar; Acar, Bilgehan Atilgan; Aytac, Emrah; Balgetir, Ferhat; Ozdemir, Atilla Ozcan (Mdpi, 2025)
Background/Objectives: The C-reactive protein-to-lymphocyte ratio (CLR) has emerged as an inflammatory biomarker reflecting innate and adaptive immune responses. Its prognostic value in acute ischemic stroke patients undergoing mechanical thrombectomy remains unclear. This study investigated whether CLR predicts functional outcome, mortality, and symptomatic intracranial hemorrhage (sICH). Methods: In this multicenter retrospective study, 714 patients with anterior circulation large-vessel occlusion treated with mechanical thrombectomy between January 2024 and January 2025 were analyzed. Clinical, angiographic, and laboratory data, including CLR, were collected. CLR was calculated as CRP divided by lymphocyte count/1000. Outcomes were 90-day modified Rankin Scale (mRS; poor outcome = 3-6; mortality = 6) and sICH per ECASS II. Receiver operating characteristic (ROC) analyses identified optimal CLR cut-offs. Logistic regression analyses determined independent predictors of outcomes. Results: sICH occurred in 39 patients (5.5%). CLR correlated with higher baseline NIHSS and lower ASPECTS. ROC analyses showed that CLR predicted poor functional outcome and mortality with an identical cut-off (>= 7.51; AUCs 0.634 and 0.664), and demonstrated strong discrimination for sICH (cut-off >= 10.64; AUC 0.855). In multivariable analyses, CLR remained an independent predictor across all outcomes (ORs 1.02, 1.02, and 1.03, all p < 0.001), in addition to established clinical factors. Conclusions: Admission CLR was independently associated with poor outcomes, mortality, and sICH after mechanical thrombectomy. As an easily obtainable marker from routine laboratory tests, CLR may provide additional prognostic information and complement established predictors, but prospective validation is required.
Keywords: acute ischemic stroke; mechanical thrombectomy; C-reactive protein-to-lymphocyte ratio; prognosis; intracranial hemorrhage